Catalisadores nanoestruturados de titânio impregnado com nanopartículas de óxido de cobal e/ou óxido de magnésio - Gonçalves, Alécia Maria (2011)
The reaction of steam reforming of ethanol is a way produce hydrogen gas, but it is essential to use catalysts to facilitate this reaction. This paper proposes the preparation of nanostructured catalysts impregnated with titanium oxide nanoparticles of cobalt and/or magnesium oxide. From the results of XRD, TEM and BET titanium oxide (anatase - T) obtained from the sol-gel method showed particles with crystallite size of 5-8 nm and a specific surface area of 258 m2g-1. The sodium titanate nanotubes were synthesized by alkaline hydrothermal treatment of titanium oxide in anatase phase, commercial (NT) and synthesized (NTS), resulting in nanotubes with outer diameter from 10 to 30 nm and length of 45 to 110 nm. The impregnation process of the oxides of cobalt and/or magnesium did not cause structural changes in the supports, and present level of metal below the desired level. Profiles of temperature programmed reduction showed the presence of cobalt oxide in the impregnated catalysts. The catalysts evaluated in the reaction of reforming ethanol (Co3O4, NT, NTCo, NTMgCo, and NTMgCo700 NTSMgCo) had ethanol conversion close to 100%, and the catalysts NTSMgCo, NTMgCo700 showed higher selectivity to 87.8% and 89,2%, respectively. With the exception of NT and NTCo catalysts showed no formation of ethylene. The amount of carbon after the catalytic tests ranged from 3.4 to 12.9 (%m/m/h).